2010
DOI: 10.1002/zoo.20282
|View full text |Cite
|
Sign up to set email alerts
|

Contrafreeloading in grizzly bears: implications for captive foraging enrichment

Abstract: Although traditional feeding regimens for captive animals were focused on meeting physiological needs to assure good health, more recently emphasis has also been placed on non-nutritive aspects of feeding. The provision of foraging materials to diversify feeding behavior is a common practice in zoos but selective consumption of foraging enrichment items over more balanced "chow" diets could lead to nutrient imbalance. One alternative is to provide balanced diets in a contrafreeloading paradigm. Contrafreeloadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 78 publications
6
70
0
Order By: Relevance
“…After it was first described in rats by Jensen (1963), this apparently paradoxical effect has been demonstrated in several species (Bean et al, 1999;de Jonge et al, 2008;Inglis et al, 1997;Lindqvist et al, 2002;McGowan et al, 2010;Menzel, 1991;Reinhardt, 1994;Rozek and Milam, 2011). Inglis et al (1997) have summarised the major explanations for contrafreeloading: (1) aspects of the earned food alternative become endowed with secondary rewarding value sufficient to maintain the costly performance; (2) neophobic tendencies cause withdrawal from free food offered in a familiar "working" context; (3) stimulus change associated with earned food increases its rewarding value; (4) working for food, especially if this means the performance of species-typical behaviour, may be reinforcing in its own right; (5) the Information Primacy Hypothesis states that contrafreeloading is adaptive in a natural environment, since it is advantageous for a wild animal to invest a certain amount of energy searching for possible future food sites.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…After it was first described in rats by Jensen (1963), this apparently paradoxical effect has been demonstrated in several species (Bean et al, 1999;de Jonge et al, 2008;Inglis et al, 1997;Lindqvist et al, 2002;McGowan et al, 2010;Menzel, 1991;Reinhardt, 1994;Rozek and Milam, 2011). Inglis et al (1997) have summarised the major explanations for contrafreeloading: (1) aspects of the earned food alternative become endowed with secondary rewarding value sufficient to maintain the costly performance; (2) neophobic tendencies cause withdrawal from free food offered in a familiar "working" context; (3) stimulus change associated with earned food increases its rewarding value; (4) working for food, especially if this means the performance of species-typical behaviour, may be reinforcing in its own right; (5) the Information Primacy Hypothesis states that contrafreeloading is adaptive in a natural environment, since it is advantageous for a wild animal to invest a certain amount of energy searching for possible future food sites.…”
Section: Introductionmentioning
confidence: 90%
“…Inglis et al (1997) suggested that, as optimal foraging and learning paradigms predict a total preference for the free food, any deviation from such an outcome should be explained using other theories. In the present study we shall consider contrafreeloading as any level of effort invested in obtaining a resource in the presence of this resource available in an easily accessible form (McGowan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the claim that CFL has an adaptive function may appear counterintuitive, data showing that CFL is highly preserved across species (Singh 1970;Tarte 1981;McGowan et al 2010;Ogura 2011) supports the view that this behavior serves a specific evolutionary function. Within this framework, the information primacy theory of CFL (Inglis and Ferguson 1986) posits that subjects placed in uncertain Electronic supplementary material The online version of this article (doi:10.1007/s00213-015-4150-4) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 90%
“…Applied behavior analysis is one of the tools that facilitates the use of innovative exhibitory and helps to define useful behavioral concepts such as "contrafreeloading" (Kinzley 2009;McGowan et al 2010;Meehan and Mench 2007;Sommerfeld et al 2006), whereby animals prefer to work for food rather than have it available ad lib. Zoo and aquarium animals have to be trained to experience the environmental opportunities provided by innovations such as exhibit rotation, computerized feeding devices, and elevated, tubular pathways that generate movement and promote exploration beyond the primary exhibit (Maple and Perdue 2013;Markowitz 1973Markowitz , 2011Markowitz and Aday 1998).…”
Section: A Current Working Model In San Franciscomentioning
confidence: 99%